ANALISIS FENOMENA I’JAZ AL – BAYANI DALAM NAZM (SUSUNAN) AL- QUR’AN - M. Rivan Febriansyah Harahap; M. Habib AlHabsyi, Harun Al Rasyid (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2024)
The aim of this research is to describe the phenomenon of ljaz Al-Bayani in the Al- Quran, which refers to the special features of language and word formation which are considered as evidence of the divinity of the Al-Quran in Islamic beliefs. This concept involves two important aspects: first, "ljaz" which denotes lying or guaranteeing humans to emulate or imitate, and second, "Al-Bayani" which refers to expression or embodying. This research uses qualitative methods with a focus on literature study as the main informant. Data collection techniques by collecting journals, books, and articles that support this research. The study's conclusion demonstrates that the idea of Ijaz Al-Bayani is implied by the following three factors (1) the Quran's intricate structure; (2) the accuracy with which words are chosen and the congruence of meaning and truth. Evidence of the human race's incapacity to equal the magnificence of the Qur'an in its succession (nadzam), which is exclusive to the Quran and fortifies the conviction that the message it contains is both profound and true.